Metal ink suitable for surface conductive functionalization of water treatment ceramic membrane and preparation method of metal ink
By using metal ink to spray printing technology on the surface of the ceramic membrane to form a conductive layer, the existing conductive ceramic membrane costs and complex production are solved, and the high -efficiency conductive functionalization of ceramic membranes and the reservation of breathable water filtration performance are realized.
Patent Information
- Application Number
- CN202411546019.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing conductive ceramic films are costly and complex in production processes, making it difficult to effectively remove small molecule organic pollutants such as PFAS in water.
A metal ink is used to paint it on the surface of the ceramic membrane by spraying printing technology to form a conductive layer. The metal ink consists of soluble organic copper salt, organic amine, inorganic ammonium salt, gallery oxide, polytamide ultra -fine powder, ethanol, and water. It ensures the uniform dispersing of each raw material through ultrasonic oscillating technology.
The conductive functionalization of the ceramic membrane surface is realized, the amount of conductive substance is reduced, the production cost is reduced, and the permeability water filtration performance of the ceramic film can be retained, which can effectively remove the organic matter that is difficult to remove in the water.
Abstract
Description
Technical Field
[0001] The invention relates to the field of water treatment and ceramic membrane surface functionalization, and in particular to a metal ink suitable for conductive functionalization of a water treatment ceramic membrane surface and a preparation method thereof. Background Art
[0002] Ceramic membrane water treatment technology is an advanced water treatment technology that uses the microporous structure of ceramic membranes to filter out impurities, pollutants and micro-objects in water. Ceramic membranes are strong and durable, but they are easily contaminated during actual use. The conventional solution to the membrane contamination problem is to backwash regularly or according to monitoring indicators. However, on the one hand, backwashing requires downtime, which affects water treatment efficiency. On the other hand, backwashing not only consumes a large amount of water but also easily causes contamination of the inner surface of the membrane. In addition, in addition to the membrane contamination problem, conventional ceramic membranes used in water filtration and purification also have the problem of difficulty in removing some small molecular organic pollutants, such as perfluoroalkyl and polyfluoroalkyl compounds (PFAS), which have been proven to be "permanent chemicals" that are harmful to both humans and the environment. It is difficult to remove the tiny PFAS in water by physical filtration alone.
[0003] In response to the above problems, researchers have proposed using ceramic membranes with conductive functions for water treatment. On the one hand, it can filter out impurities and pollutants. On the other hand, after the ceramic membrane is energized, it can effectively remove organic matter, colloids, etc. in the water that are difficult to remove by filtering alone, and can greatly reduce the pollution of pollutants to the membrane. Existing conductive ceramic membranes generally use conductive materials to dope ceramic slurry, and then sinter to form conductive ceramic membranes with conductive functions. The shortcomings are: the conductive material is evenly dispersed in the entire ceramic membrane, so the amount of conductive material is large, resulting in a high cost of conductive ceramic membranes; due to the change in the composition of the ceramic slurry, the process parameters and equipment requirements during production have changed, resulting in the original process and equipment cannot be used, and the investment cost of process and equipment improvement is high. Therefore, it is necessary to provide a metal ink that can make the surface of the water treatment ceramic membrane conductive, which can be used to spray the surface of the finished ceramic membrane to form a conductive membrane without affecting the original water filtration treatment function of the ceramic membrane. Summary of the invention
[0004] The present invention provides a metal ink suitable for conductive functionalization of the surface of a water treatment ceramic membrane and a preparation method thereof, aiming to overcome the above-mentioned deficiencies in the prior art.
[0005] The technical solution of the present invention to solve the above technical problems is as follows: a metal ink suitable for conductive functionalization of the surface of a water treatment ceramic membrane, which consists of a soluble organic copper salt, an organic amine, an inorganic ammonium salt, graphene oxide, polyimide ultrafine powder, ethanol and water, wherein the mass ratio of the inorganic ammonium salt, graphene oxide, polyimide ultrafine powder and the soluble organic copper salt is (0.05-0.08): (0.02-0.04): (0.03-0.06): 1, the volume ratio of ethanol and water is 0.3-0.5: 1, the dosage ratio of the soluble organic copper salt to water is 0.12-0.25g: 1mL, and the molar ratio of copper ions of the soluble organic copper salt to the organic amine is 1: 1-4.
[0006] On the basis of the above technical solutions, the present invention can also have the following further specific options.
[0007] Specifically, the soluble organic copper salt is copper acetate or copper formate, preferably copper acetate.
[0008] Specifically, the organic amine is ethylenediamine or ethanolamine, preferably ethylenediamine.
[0009] Specifically, the inorganic ammonium salt is ammonium chloride.
[0010] Specifically, the graphene oxide is a single layer or a few layers of graphene oxide with a thickness of less than 5 nm, preferably a single layer of graphene oxide with a thickness of less than 1.2 nm.
[0011] Specifically, the polyimide ultrafine powder is a thermosetting resin, and the average particle size is 30-40 μm.
[0012] Preferably, the mass ratio of inorganic ammonium salt, graphene oxide, polyimide ultrafine powder and soluble organic copper salt is 0.06:0.03:0.04:1.
[0013] The present invention also provides a method for preparing a metal ink suitable for conductive functionalization of the surface of a water treatment ceramic membrane, which comprises the following steps:
[0014] First, according to the dosage ratio recorded in the above formula, corresponding amounts of soluble organic copper salt, organic amine, inorganic ammonium salt, graphene oxide, polyimide ultrafine powder, ethanol and water are taken; then, ethanol and water are mutually dissolved to obtain a mixed solvent, graphene oxide is dissolved in the mixed solvent under stirring conditions, the temperature is raised to 45-55° C. and polyimide ultrafine powder, inorganic ammonium salt and organic amine are added in sequence under ultrasonic vibration conditions, after the addition is completed, a mixed solution is obtained, and ultrasonic vibration is continued for 2-4 hours to evenly disperse the raw materials in the mixed solution, and finally, the soluble organic copper salt is added to the mixed solution in multiple times at 40-50° C. and ultrasonic vibration conditions, after the addition is completed, ultrasonic vibration is continued for 1.5-3 hours, and then naturally cooled to room temperature to obtain the obtained product.
[0015] Specifically, the ultrasonic power during ultrasonic oscillation is 120-160W, and the ultrasonic frequency is 35-45KHz.
[0016] Specifically, the soluble organic copper salt is added to the mixed solution at least three times, and each time the mixture is added, the mixture is subjected to ultrasonic oscillation for more than 0.5 h before the next addition.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] The present invention uses soluble organic copper salt and organic amine to generate organic complex copper and dissolves and disperses it in an alcohol-water mixed solvent, and cooperates with the dispersing effect of graphene oxide to effectively increase the copper content in the metal ink. The inorganic ammonium salt decomposes when the metal ink is sprayed on the surface of the ceramic membrane and heated and cured to generate gas. On the one hand, the pores of the membrane are enriched after forming to retain the air permeability and water filtration ability of the ceramic membrane. On the other hand, the ammonia released by the ammonia and the ammonia generated by the decomposition of the organic complex copper in an air-isolated environment can reduce the copper ions to metal Copper and graphene oxide are reduced to graphene to form a two-component conductive layer of copper and graphene, ensuring excellent conductive properties; an appropriate amount of polyimide ultrafine powder is stably dispersed in an alcohol-water solvent under the dispersing function of graphene oxide. When heated and cured to form a film, the polyimide undergoes a process of first softening and melting and then solidifying and forming, which enables copper and graphene to combine with each other and firmly adhere to the surface of the ceramic membrane to form a conductive layer with excellent performance. At the same time, after curing, the polyimide is resistant to high temperature, chemical corrosion and has strong mechanical strength, which is particularly suitable for the use environment of water treatment ceramic membranes. DETAILED DESCRIPTION
[0019] The present invention is further described in detail below in conjunction with specific embodiments. The examples are only used to explain the present invention and are not used to limit the scope of the present invention.
[0020] To avoid redundant description, the drugs used in the following examples are all commercially available products unless otherwise specified; the methods used are all conventional methods in the art unless otherwise specified.
[0021] The invention provides a metal ink suitable for conductive functionalization of the surface of a water treatment ceramic membrane. The metal ink consists of a soluble organic copper salt, an organic amine, an inorganic ammonium salt, graphene oxide, polyimide ultrafine powder, ethanol and water, wherein the mass ratio of the inorganic ammonium salt, graphene oxide, polyimide ultrafine powder and the soluble organic copper salt is (0.05-0.08):(0.02-0.04):(0.03-0.06):1, the volume ratio of ethanol to water is 0.3-0.5:1, the dosage ratio of the soluble organic copper salt to water is 0.12-0.25 g:1 mL, and the molar ratio of copper ions of the soluble organic copper salt to the organic amine is 1:1-4. Among them, the soluble organic copper salt is copper acetate; the organic amine is preferably ethylenediamine or ethanolamine; the inorganic ammonium salt is ammonium chloride; the graphene oxide is preferably single-layer graphene; the polyimide is preferably an ultrafine powder with an average particle size of 30-40 μm, and a thermosetting resin is selected.
[0022] The above-mentioned metal ink is prepared in combination with specific embodiments below.
[0023] Example 1
[0024] A metal ink suitable for conductive functionalization of the surface of a water treatment ceramic membrane, the preparation method of which is as follows:
[0025] First, ammonium chloride, monolayer graphene oxide powder, polyimide ultrafine powder and copper acetate are weighed in a weight ratio of 0.06:0.03:0.04:1 for use, and distilled water is taken in a ratio of 0.18 g:1 mL of copper acetate to water, ethylenediamine is taken in a molar ratio of 1:2 of copper acetate to ethylenediamine, and ethanol is weighed in a volume ratio of 0.4:1 of ethanol to water; then, ethanol and water are first dissolved in each other to obtain a mixed solvent, the monolayer graphene oxide is dissolved in the mixed solvent under stirring conditions, the temperature is raised to 45-50°C, and the mixture is stirred at ultra-high temperature. Under ultrasonic oscillation conditions with an acoustic power of 120-140W and an ultrasonic frequency of 35-40KHz, polyimide ultrafine powder, ammonium chloride and ethylenediamine are added in sequence. After the addition is completed, a mixed solution is obtained, and ultrasonic oscillation is continued for 4 hours to evenly disperse the raw materials in the mixed solution. Finally, copper acetate is divided into three parts and added to the mixed solution in 3 times at 45-50°C and ultrasonic oscillation conditions. After each addition, ultrasonic oscillation is performed for 0.5h before the next addition. After the addition is completed, ultrasonic oscillation is continued for 2h, and then naturally cooled to room temperature to obtain the product.
[0026] Example 2
[0027] A metal ink suitable for conductive functionalization of the surface of a water treatment ceramic membrane, the preparation method of which is as follows:
[0028] First, ammonium chloride, monolayer graphene oxide powder, polyimide ultrafine powder and copper acetate were weighed in a weight ratio of 0.05:0.02:0.03:1, and distilled water was taken in a ratio of 0.25 g:1 mL of copper acetate to water, ethylenediamine was taken in a molar ratio of 1:2 of copper acetate to ethylenediamine, and ethanol was weighed in a volume ratio of 0.3:1 of ethanol to water; then, ethanol and water were first dissolved in each other to obtain a mixed solvent, the monolayer graphene oxide was dissolved in the mixed solvent under stirring conditions, the temperature was raised to 45-50°C, and ultrasonic waves were used to stir the mixed solvent. Under ultrasonic oscillation conditions with a power of 120-140W and an ultrasonic frequency of 35-40KHz, polyimide ultrafine powder, ammonium chloride and ethylenediamine are added in sequence. After the addition is completed, a mixed solution is obtained, and ultrasonic oscillation is continued for 3 hours to evenly disperse the raw materials in the mixed solution. Finally, copper acetate is divided into three parts and added to the mixed solution in 3 times at 45-50°C and ultrasonic oscillation conditions. After each addition, ultrasonic oscillation is carried out for 1 hour before the next addition. After the addition is completed, ultrasonic oscillation is continued for 1.5 hours, and then it is naturally cooled to room temperature to obtain the product.
[0029] Example 3
[0030] A metal ink suitable for conductive functionalization of the surface of a water treatment ceramic membrane, the preparation method of which is as follows:
[0031] First, ammonium chloride, monolayer graphene oxide powder, polyimide ultrafine powder and copper acetate were weighed in a weight ratio of 0.07:0.03:0.05:1, and distilled water was taken in a ratio of 0.20 g:1 mL of copper acetate to water, ethylenediamine was taken in a molar ratio of 1:2 of copper acetate to ethylenediamine, and ethanol was weighed in a volume ratio of 0.4:1 of ethanol to water; then, ethanol and water were first dissolved in each other to obtain a mixed solvent, the monolayer graphene oxide was dissolved in the mixed solvent under stirring conditions, the temperature was raised to 50-55°C, and ultrasonic waves were used to stir the mixed solvent. Under ultrasonic oscillation conditions with a power of 140-160W and an ultrasonic frequency of 40-45KHz, polyimide ultrafine powder, ammonium chloride and ethylenediamine are added in sequence. After the addition is completed, a mixed solution is obtained, and ultrasonic oscillation is continued for 2 hours to evenly disperse the raw materials in the mixed solution. Finally, copper acetate is divided into three parts and added to the mixed solution in 3 times at 40-45°C and ultrasonic oscillation conditions. After each addition, ultrasonic oscillation treatment is performed for more than 0.5h before the next addition. After the addition is completed, ultrasonic oscillation is continued for 3 hours, and then naturally cooled to room temperature to obtain the product.
[0032] Example 4
[0033] A metal ink suitable for conductive functionalization of the surface of a water treatment ceramic membrane, the preparation method of which is as follows:
[0034] First, ammonium chloride, monolayer graphene oxide powder, polyimide ultrafine powder and copper acetate were weighed in a weight ratio of 0.08:0.04:0.06:1, and distilled water was taken in a ratio of 0.12 g:1 mL of copper acetate to water, ethylenediamine was taken in a molar ratio of 1:2 of copper acetate to ethylenediamine, and ethanol was weighed in a volume ratio of 0.5:1 of ethanol to water; then, ethanol and water were first dissolved in each other to obtain a mixed solvent, the monolayer graphene oxide was dissolved in the mixed solvent under stirring conditions, the temperature was raised to 50-55°C, and ultrasonic waves were used to stir the mixed solvent. Under ultrasonic oscillation conditions with a power of 140-160W and an ultrasonic frequency of 40-45KHz, polyimide ultrafine powder, ammonium chloride and ethylenediamine are added in sequence. After the addition is completed, a mixed solution is obtained, and ultrasonic oscillation is continued for 3 hours to evenly disperse the raw materials in the mixed solution. Finally, copper acetate is divided into three parts and added to the mixed solution in 3 times at 40-45°C and ultrasonic oscillation conditions. After each addition, ultrasonic oscillation treatment is performed for more than 0.5h before the next addition. After the addition is completed, ultrasonic oscillation is continued for 3 hours, and then it is naturally cooled to room temperature to obtain the product.
[0035] The metal conductive inks prepared in Examples 1 to 4 were used as samples, and a wet film layer with a thickness of 1-5 μm was formed on the surface of the ceramic substrate by inkjet printing. Then, the film layer was slowly heated to 190°C for drying under nitrogen protection and air isolation, and then heated to 350°C for sintering and curing. Finally, the film layer was quickly heated to 420°C and maintained for 2-3 minutes, and naturally cooled to room temperature, so that a conductive film layer with a thickness of about 0.5-3 μm and stable adhesion to the ceramic substrate was formed on the surface of the ceramic substrate. Due to the decomposition of ammonium chloride and organic complex copper, the conductive film layer had abundant pores and had good air permeability and water filtration performance. After testing, taking the conductive film layer prepared by the metal conductive ink corresponding to Example 1 as an example, its conductivity was measured to reach 12643.5S / m, and the conductive performance was good.
[0036] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A metal ink suitable for conductive functionalization of the surface of a water treatment ceramic membrane, characterized in that: The invention is composed of soluble organic copper salt, organic amine, inorganic ammonium salt, graphene oxide, polyimide ultrafine powder, ethanol and water, wherein the molar ratio of copper ion of soluble organic copper salt to organic amine is 1:1-4, the mass ratio of inorganic ammonium salt, graphene oxide, polyimide ultrafine powder to soluble organic copper salt is (0.05-0.08):(0.02-0.04):(0.03-0.06):1, the volume ratio of ethanol to water is 0.3-0.5:1, and the dosage ratio of soluble organic copper salt to water is 0.12-0.25g:1mL.
2. The metal ink suitable for conductive functionalization of the surface of water treatment ceramic membrane according to claim 1, characterized in that: The soluble organic copper salt is copper acetate or copper formate.
3. The metal ink suitable for conductive functionalization of the surface of water treatment ceramic membrane according to claim 1, characterized in that: The organic amine is ethylenediamine or ethanolamine.
4. The metal ink suitable for conductive functionalization of the surface of water treatment ceramic membrane according to claim 1, characterized in that: The inorganic ammonium salt is ammonium chloride.
5. The metal ink suitable for conductive functionalization of the surface of water treatment ceramic membrane according to claim 1, characterized in that: Graphene oxide is a single layer or a few layers of graphene oxide with a thickness of less than 5 nm.
6. The metal ink suitable for conductive functionalization of the surface of water treatment ceramic membrane according to claim 1, characterized in that: The polyimide ultrafine powder is a thermosetting resin with an average particle size of 30-40 μm.
7. The metal ink suitable for conductive functionalization of the surface of water treatment ceramic membrane according to claim 1, characterized in that: The mass ratio of inorganic ammonium salt, graphene oxide, polyimide ultrafine powder and soluble organic copper salt is 0.06:0.03:0.04:
1.
8. A method for preparing a metal ink suitable for conductive functionalization of the surface of a water treatment ceramic membrane, characterized in that: The steps include: First, according to the dosage ratio in any one of claims 1 to 7, corresponding amounts of soluble organic copper salt, organic amine, inorganic ammonium salt, graphene oxide, polyimide ultrafine powder, ethanol and water are taken; then, ethanol and water are mutually dissolved to obtain a mixed solvent, graphene oxide is dissolved in the mixed solvent under stirring conditions, the temperature is raised to 45-55° C. and polyimide ultrafine powder, inorganic ammonium salt and organic amine are added in sequence under ultrasonic vibration conditions, after the addition is completed, a mixed solution is obtained, and ultrasonic vibration is continued for 2-4 hours to uniformly disperse the raw materials in the mixed solution, and finally the soluble organic copper salt is added to the mixed solution in multiple times at 40-50° C. and ultrasonic vibration conditions, after the addition is completed, ultrasonic vibration is continued for 1.5-3 hours, and then naturally cooled to room temperature to obtain.
9. The method for preparing a metal ink suitable for conductive functionalization of the surface of a water treatment ceramic membrane according to claim 8, characterized in that: The ultrasonic power during ultrasonic oscillation is 120-160W, and the ultrasonic frequency is 35-45KHz.
10. The method for preparing a metal ink suitable for conductive functionalization of the surface of a water treatment ceramic membrane according to claim 8, characterized in that: The soluble organic copper salt is added to the mixed solution at least three times, and each time it is added, it is subjected to ultrasonic oscillation treatment for more than 0.5 h before the next addition.